THE INTEGRATION OF COOPERATIVE LEARNING MODEL ON ENGLISH LANGUAGE LEARNING IN FOSTERED ELEMENTARY SCHOOL OF SIMALUNGUN UNIVERSITY - Silalahi, Mardin; Siregar, Geby Arni; Naibaho, Lamhot (English Review: Journal of English Education, 2023)
Abstract: This research is aimed at analyzing the integration of the cooperative learning model into English language learning, which was done at fostered elementary school of Simalungun University. The method of the study used was a quasi-experimental research method with a post-test-only control group design. The population of this study was all elementary school learners assisted by Simalungun University in Siantar City, with as many as 232 people. The research sample chosen was 70 learners, determined by using random sampling. The researcher used a lottery system to appoint the experimental and control classes. Based on the lottery system that was carried out, it was found that class IV of school X served as the experimental group and class IV Class Y as the control group. The instrument of the research was two sets of previously validated questionnaires. The data technique analysis used was statistical analysis. The result of the study is that the motivation and learning outcomes of learners following the NHT cooperative learning model were higher than learners following the conventional learning model. It is concluded that NHT cooperative learning model has a positive effect on increasing achievement motivation and English learning outcomes for learners of class IV at Y and X Schools both separately and simultaneously.Keywords: Cooperative learning; learning english; number head together